Evaluation of the Semantic Dynamics of Educational Space of University in the Process of Nurturing Critical Thinking in Students of Liberal Arts and Sciences Programme - Polyanina O.I; Baleva M.V; Shevkova E.V (Moscow State University of Psychology and Education, 2018)
The study is devoted to the analysis of the connotative dynamics of the concepts describing the educational space of university in students of Liberal Arts and Sciences degree programme who took a course in "Thinking and Writing". The hypothesis tested was that there would be a dynamic trend towards greater differentiation and individualization of concepts "student", "learning" and "training group" in the experimental group as compared to the control sample. The participants (152 students, including 126 females and 26 males aged from 17 to 23, M = 17.91, SD = 0.79) evaluated these concepts using the Semantic Differential Scale before and after the course. It was found (p <0.10 ÷ 0.05) that in the experimental sample the connotations for "student" showed an increase in imagery and subjective evaluation component, and the concept "learning" was assessed as less hostile and more diverse. In turn, the connotative dynamics of the meanings for "training group" was similar to that of the control group. The obtained results are of primary interest in the context of shaping the students' learning motivation and can be employed in comparative studies of the effects produced by conceptually different educational programs.